2017
DOI: 10.1111/ejh.12925
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free DNA — Minimally invasive marker of hematological malignancies

Abstract: Although tumor cells are the most reliable source of tumor DNA, biopsy of the tumor is an invasive procedure that should be avoided in some cases. The main limitation of any biopsy is sampling of one tumor site, which may not represent all malignant clones due to the heterogeneity of the tumor. These clones respond to treatment differently and thus directly influence survival of the patient. Circulating cell-free DNA (cfDNA) is released from multiple tumor sites, reflects overall heterogeneity of the tumor, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…It provides non‐ or minimally invasive alternative to diagnosis, treatment monitoring and MRD monitoring from body fluids . One of the most promising target molecules in liquid biopsies are cell‐free DNA (cfDNA), short double‐stranded DNA molecules circulating in various body fluids . Low levels of these molecules can be found even in healthy individuals; however, levels of cfDNA were found to be considerably elevated in various pathological conditions .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It provides non‐ or minimally invasive alternative to diagnosis, treatment monitoring and MRD monitoring from body fluids . One of the most promising target molecules in liquid biopsies are cell‐free DNA (cfDNA), short double‐stranded DNA molecules circulating in various body fluids . Low levels of these molecules can be found even in healthy individuals; however, levels of cfDNA were found to be considerably elevated in various pathological conditions .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising target molecules in liquid biopsies are cell‐free DNA (cfDNA), short double‐stranded DNA molecules circulating in various body fluids . Low levels of these molecules can be found even in healthy individuals; however, levels of cfDNA were found to be considerably elevated in various pathological conditions . The use of cfDNA for MRD evaluation in various hematological malignancies was described several times as having promising results .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not yet implemented for childhood ALL, the development of new methods using circulating DNA could provide less invasive approaches . Indeed, these techniques use a small amount of plasma in which abnormal DNA issued from the tumor cells is amplified and characterized.…”
Section: Mrd Assessmentmentioning
confidence: 99%
“…Liquid biopsies (biopsies of peripheral blood) represent a real promise for such diseases since circulating molecules detectable in peripheral blood (PB) mirror the complex heterogeneity of MG and can serve as potential diagnostic, prognostic, and predictive markers. We and others showed that these molecules include cell‐free DNA and noncoding RNA (ncRNA), especially microRNA (miRNA) and long noncoding RNA (lncRNA) . LncRNA expression is tissue specific and implicated in diverse biological functions .…”
Section: Introductionmentioning
confidence: 99%